Proof of Ecocide: Towards a Forensic Practice for the Proposed International Crime Against the Environment - Ahmed, Nabil (​Forensic Archaeology, Anthropology and Ecology, 2019)
This article discusses developments in international environmental justice alongside contemporary environmental forensics techniques. The article begins by providing an introduction to ecocide, the proposed international crime to the Rome Statute of the International Criminal Court (ICC) and the concept of the legal threshold of harm. It argues that forensic awareness has a role to play in developing new legal frameworks for the protection of the environment. It describes one particular approach to the practice of environmental investigations, using the example of remote sensing. From an international justice perspective, the concern of the present article is a discussion of how innovations in remote sensing technologies have allowed non court actors, civil society groups and nongovernmental organisations access to scientific evidence. It concludes by making recommending towards establishing forensic standards for admissible evidence of ecocide crime.